Aggresive encounter between Lagothrix flavicauda and Nasua nasua at El Toro, Amazonas, Peru - Fack, Vinciane; Shanee, Sam; Drubbel, Régine Vercauteren; Meunier, Hélène; Vercauteren, Martine (Neotropical Primates, 2018)
No abstract